Accounting Information Systems as a Tool for Effective Petty Cash Control: Evidence from a Hotel Case Study - Irfanaja Rohim, Nadhira; Rose, Maria; Mayardit, Fatimah Kiir (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
This study investigates the role of accounting information systems (AIS) in controlling petty cash disbursements within the hospitality industry, specifically through the implementation of a fluctuating fund-balance system at Hotel X in Surabaya. Utilizing a descriptive qualitative approach, the research involved data collection through interviews, observations, and documentation over five months. The results indicate that Hotel X manages petty cash disbursements via two distinct methods based on fund holders: the general cashier and the front office, with each method serving different types of expenses. The fluctuating fund-balance system adjusts petty cash balances according to operational needs, which provides flexibility while enhancing control over cash flow. However, findings revealed a lack of sufficient internal controls and documentation that led to discrepancies between recorded disbursements and supporting evidence, highlighting a significant gap in cash management practices. The integration of a robust AIS helps mitigate these challenges by improving internal controls, reducing fraud risks, and ensuring the reliability of financial reporting. This research contributes to the literature on AIS by demonstrating its utility in petty cash management, underscoring its importance for operational efficiency and financial security in the hospitality sector. The findings suggest that adopting such a system can lead to improved financial accountability and better adherence to internal control standards in cash handling.